The Impact of Social Stigma on Child Patients with Cleft Lip and Palate - Ariani, Yuni; Astarini, Diska (Folia Medica Indonesiana, 2023)
Highlights: 1. Awareness of social stigma impact on children with cleft lip and palate is lacking in various areas. 2. Identifying social stigma's influence on children with cleft lip is important to help surgeons prioritize resource allocation and provide further evidence in incorporating quality of life. Abstract: Social rejection still happens to a large number of children who have cleft lip and palate. Stigma has a detrimental impact on children with cleft in the aspects of education, employment, marriage, and community acceptance, which can be exacerbated by barriers to high-quality child care. A literature study related to this topic was conducted by searching for articles from 2018 to October 2021 through three databases (i.e., PubMed, Embase, and Medline). The term used for the literature search was "cleft", which generated results that were sorted alphabetically and by relevance. This yielded 15 articles that focused on social stigma's influence on cleft lip and palate patients. In conclusion, the articles generally reported that the awareness of social stigma impacts on children with cleft lip and palate are lacking in various areas. It is important to identify social stigma's influence on children with cleft lip. This can help surgeons prioritize resource allocation and provide further evidence in incorporating quality of life measures into the treatment outcome assessment.